2020
DOI: 10.3389/fonc.2020.544288
|View full text |Cite|
|
Sign up to set email alerts
|

Pyruvate Kinase M2 Promotes Prostate Cancer Metastasis Through Regulating ERK1/2-COX-2 Signaling

Abstract: Pyruvate kinase M2 (PKM2) is a key enzyme of glycolysis, which is highly expressed in many tumor cells, and has emerged as an important player in tumor progression and metastasis. However, the functional roles of PKM2 in tumor metastasis remain elusive. Here we showed that PKM2 promoted prostate cancer metastasis via extracellularregulated protein kinase (ERK)-cyclooxygenase (COX-2) signaling. Based on public databases, we found that PKM2 expression was upregulated in prostate cancer and positively associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…Consistent with this finding, PKM2 expression in liver cancer cells affects the flux of glucose metabolism [37]. Another potential mechanism is also suggested by findings in prostate cancer, where PKM2 promotes metastasis by modulating the extracellular-regulated protein kinase-cyclooxygenase pathway [38].…”
Section: Discussionsupporting
confidence: 67%
“…Consistent with this finding, PKM2 expression in liver cancer cells affects the flux of glucose metabolism [37]. Another potential mechanism is also suggested by findings in prostate cancer, where PKM2 promotes metastasis by modulating the extracellular-regulated protein kinase-cyclooxygenase pathway [38].…”
Section: Discussionsupporting
confidence: 67%
“…Prostaglandin-endoperoxide synthase 2 (PTGS2), also known as cyclooxygenase-2(COX-2), a crucial enzyme in the process of arachidonic acid conversion to prostaglandins and other eicosanoids, was reported to promote malignant metastasis in colorectal tumor cells (Fenwick et al, 2003). In addition, Guo et al (2020) demonstrated that PKM2 upregulates COX-2 expression, leading to epithelialmesenchymal transition (EMT) and metastasis of PCa, by promoting the phosphorylation of ERK1/2. More studies on the role of COX-2 in the regulation of PCa metastasis are required.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data herein and overexpression of various glycolytic proteins including ALDOA and PKM2 in cancer, suggest that patients with tumors overexpressing DNA-PK and/or ALDOA/PKM2 may benefit from combination of DNA-PK and ALDOA/PKM2 inhibitors. In PCa targeting PKM2 via siRNA leads to decrease proliferation and metastasis in PCa [50,51], thus combination with DNA-PKi may show greater anti-cancerous activity. Moreover, since upregulated glycolysis is a hallmark of cancer [32], patients may benefit from combination therapy of single agent activity in vitro but its interrogation was halted in phase I/II clinical trials for treatment of solid tumors, including hormone refractory PCa, due to limited efficacy on inhibiting tumor growth and high toxicities [52].…”
Section: Combination Of Dna-pk and Glycolysis Inhibitor Decreases Proliferation In Crpcmentioning
confidence: 99%